Role of probiotics in managing various human diseases, from oral pathology to cancer and gastrointestinal diseases - Petrariu, Oana-Alina; Barbu, Ilda Czobor; Niculescu, Adelina-Gabriela; Constantin, Marian; Grigore, Georgiana Alexandra; Cristian, Roxana-Elena; Mihaescu, Grigore; Vrancianu, Corneliu Ovidiu (Frontiers in Microbiology, 2024)
The imbalance of microbial composition and diversity in favor of pathogenic microorganisms combined with a loss of beneficial gut microbiota taxa results from factors such as age, diet, antimicrobial administration for different infections, other underlying medical conditions, etc. Probiotics are known for their capacity to improve health by stimulating the indigenous gut microbiota, enhancing host immunity resistance to infection, helping digestion, and carrying out various other functions. Concurrently, the metabolites produced by these microorganisms, termed postbiotics, which include compounds like bacteriocins, lactic acid, and hydrogen peroxide, contribute to inhibiting a wide range of pathogenic bacteria. This review presents an update on using probiotics in managing and treating various human diseases, including complications that may emerge during or after a COVID-19 infection.